Use of vision-based augmented reality to improve student learning of the spine and spinal deformities. An exploratory study. - Kandasamy, Gok; Bettany-Saltikov, Josette; Cordry, Julien; McSherry, Rob (South African Journal of Physiotherapy, 2021)
Background: Knowledge of anatomy and pathology of the spine together with spinal deformities is integral to several healthcare disciplines. This knowledge is crucial for graduates for assessment and management of patients with spinal problems. Physiotherapy students generally find it difficult to conceptualise the integrity of the structure and function of the spine that affects their acquisition of related physiotherapy skills. Objective: Our first objective was to introduce and evaluate the use of a Vision-Based Augmented Reality (VBAR) mobile application to teach students the anatomy and accessory movements of the spine. A further objective was to explore student experiences of and engagement with VBAR by conducting a post-lecture survey comparing VBAR to traditional teaching. Methods: This post-intervention crossover design study included two groups: final year physiotherapy students (n = 74) and mean age of 23 (±1.8). The computing department at Teesside University developed the VBAR mobile application. Moreover, a survey adapted from a previously published article was disseminated to students to evaluate their level of understanding following the use of the VBAR application. Results: The results demonstrated that the median questionnaire scores in students' perceived level of understanding for the VBAR group were significantly higher than for the traditional teaching group (p < 0.05). Conclusion: The results of this post-intervention survey suggest that the integration of VBAR learning activities results in gains relating to students' understanding of spinal anatomy, function, pathology and deformities. These findings suggest that VBAR could be an additional teaching tool to support student learning. Clinical implications: Greater understanding is expected to increase the quality of clinical practice.